Brain Metastasis Response to Stereotactic Radio Surgery: A Mathematical Approach - Odelaisy León-Triana; Julián Pérez-Beteta; David Albillo; Ana Ortiz de Mendivil; Luis Pérez-Romasanta; Elisabet González-Del Portillo; Manuel Llorente; Natalia Carballo; Estanislao Arana; Víctor M. Pérez-García (Mathematics, 2021)
Brain metastases (BMs) are cancer cells that spread to the brain from primary tumors in other organs. Up to 35% of adult cancer patients develop BMs. The treatment of BM patients who have well-controlled extracranial disease and a small number of lesions consists of localized doses of radiation (stereotactic radio surgery (SRS)). Estimating prognosis among BM patients may allow treatments to be chosen that balance durability of intracranial tumor control with quality of life and the side effects of treatment. No mathematical model-based quantitative biomarkers have been determined for estimating prognosis. As a first step toward that goal, we describe a mathematical model of growth and response of brain metastasis to stereotactic radio surgery. The mathematical model incorporates some biological mechanisms involved in BM growth and response to SRS and allows the observed dynamics to be accurately described.